The Consequences of Compensation and Emotional Exhaustion on Job Satisfaction among Bank Employees in South Halmahera Regency - Ramli, Susmita; Soleman, Marwan Man; Nurlaila, Nurlaila (Jurnal Manajemen Sinergi, 2024)
ABSTRACTObjective: The purpose of the study is to discover and analyse the relationship between compensation and employee emotional weariness on employee job satisfaction at South Halmahera Regency Bank. The study's population consisted of bank personnel from South Halmahera Regency, North Maluku Province, including Muamalat Bank, BRI, BSI, Mandiri Bank, Maluku Bank, BNI, and Saruma Bank. The banking sector has a total of 86 employees.Methodology: The design of this research is to use a survey method, because the research approach is quantitative. To investigate the influence of the independent and dependent variables, multiple regression is employed with the statistical package for social scientists (SPSS) tool. Findings: Compensation for job satisfaction results show t count - t table 1.664 and sig. 0.05, then Ha is accepted and Ho is rejected; emotional exhaustion on satisfaction results show that t count t table 1.664, and the significant value 0.05, then Ha is accepted and Ho is rejected.Conclusion: Remuneration has a negative and large impact on job satisfaction among South Halmahera Regency Bank employees. Emotional exhaustion has a negative and significant effect on the job satisfaction of South Halmahera district bank employees, which means that if employees are emotionally exhausted, their job satisfaction decreases, and if they are not emotionally exhausted, their job satisfaction rises.